The political economy of punishment and the penal state in Latin America - Iturralde Sánchez, Manuel A. (Tracing the relationship between inequality, crime, and punishment, 2020)
In both criminology and the sociology of punishment there has been a rebirth of the political economy of crime and punishment, where the relationship between these phenomena and levels of inequality within a given society is a key aspect, to assess the transformation and features of the crime control fields of contemporary societies and to relate them to different typologies. This chapter will discuss and problematize this perspective through the analysis of Latin American crime control fields. Considering the flaws of general typologies, usually coming from the global north, the chapter will stress the need for a more detailed comparative analysis of the penal state and the institutional structures, dynamics and dispositions present in every jurisdiction, in both the global north and south, that have a direct impact on penal policy and its outcomes.